On the value of a reliability‐based nonlinear finite element analysis approach in the assessment of concrete structures. (25th June 2019) - Slobbe, Arthur; Rózsás, Árpád; Allaix, Diego L.; Bigaj‐van Vliet, Agnieszka
Abstract: The objective of this paper is to explore the value of reliability‐based nonlinear finite element analysis (NLFEA) over the currently available, standardized assessment methods. To our knowledge, no studies are available on this subject, and this paper provides a first insight into the value and reliability level of these assessment methods. The exploration is illustrated through three reinforced concrete structural members: a continuous girder, a continuous deep beam, and a high‐strength deep beam. The analysis is performed gradually: step by step advancing the approximation level of the mechanical and the probabilistic models. The added value of the reliability‐based NLFEA over the semi‐probabilistic Eurocode (EC) method is found to be on average 0.60. In other words: even if according to the semi‐probabilistic EC method the design action ( E d ) is 60% higher than the design resistance ( R d ), the compliance with the target reliability criterion can be demonstrated by a reliability‐based NLFEA. Furthermore, it is observed that the gain and its cause (i.e., more advanced mechanical or probabilistic models) are different for the three cases. Though this outcome is restricted to the analyzed cases and should be interpreted as an upper limit added value, it indicates that a more detailed physical representation of the problem and an explicit treatment of uncertainties may uncover substantial reserves compared with the currently available, standardized assessment methods. Hence, the reliability‐based NLFEA method offers a promising alternative in the assessment of existing structures, enabling to avoid expensive measures that might be needed based on simplified methods.